Critical assessment of the Rolfe-Novak CVN-KIC upper shelf correlation. (December 2021) - Wallin, Kim
Highlights: The original Rolfe – Novak KIc – CVN correlation is not applicable for real applications. KIc – CVN correlations are affected by specimen size. A new size insensitive correlation between KIsi (and KJIc ) and CVN for high strength steels is proposed. Abstract: The Rolfe-Novak correlation, was the first attempt to relate Charpy-V impact energy to a fracture mechanical material parameter. They tested 11 materials with variable yield strength, mainly in the range 1000–1300 MPa. This data was used to develop a correlation between Charpy-V notch energy and linear elastic fracture toughness KIc . The correlation is considered as base for high strength steel CVN-KIc correlations still today. The historic Rolfe – Novak fracture toughness data are here re-analyzed based on present understanding of fracture mechanics. It is shown that the original results were affected by different specimen sizes, shallow flaw effects, varying degree of plasticity and a non-systematic and non-standard engineering definition of fracture toughness KIc . The data has been re-evaluated in terms of the new size-independent fracture toughness definition KIsi, now described in ASTM E399. Based on the re-evaluation a new physically sound correlation between CVN and KIsi is determined. KIsi is shown to be close to KJIc according to ASTM E1820 for high strength steels.